Recoding the Saccharomyces cerevisiae genome - Silva, Ana Rita Guimarães Rodrigues da (2023)
The genetic code is considered one of the most conserved, even immutable, features of life. However, numerous deviations from its canonical form were discovered across the three domains of life over the last 40 years, highlighting the unexpected flexibility of this central process of life. These discoveries and previous work from our laboratory on the evolution of the genetic code inspired this PhD thesis. We explored the hypothesis that synthetic codon ambiguities combined with experimental evolution could lead to the reassignment of rare codons in the yeast S. cerevisiae. For this, we replaced the leucine-CUC decoding tRNA with a mutant serine tRNA, producing yeast strains that incorporate up to 50% of Ser at thousands of Leu-CUC sites, across the entire yeast proteome. Despite the associated high fitness cost, recombinant cells were highly tolerant and capable of adapting to high level Ser incorporation at CUC codons in a long-term evolutionary experiment. We found that adaptation to high Leu-to-Ser mistranslation triggered significant genomic alterations. Indeed, ploidy shifts, increased occurrence of copy number variation (CNVs) events, and aneuploidies were common in the recombinant yeast strains. Transcriptome and translatome analyses identified upregulated ribosomal proteins (RPs) as an unexpected player in the adaptation of yeast to Leu-to-Ser mistranslation at CUC sites. Contrary to expectation, the overexpression of RPs did not increase the protein synthesis rate, and it remains unclear how they contribute to CUC reprogramming or stress tolerance. By achieving 50% of Ser incorporation at Leu-CUC sites on a proteome wide scale, this project pushed the limit of sense codon ambiguity to unprecedented levels, showcasing both its plasticity and the impressive tolerance of yeast to translational errors. It also demonstrates the wide-reaching potential of this approach in synthetic biology and provides new clues about the biology of protein synthesis errors. Moreover, by expanding our understanding of the long-term effects of protein misfolding and aggregation, this work also contributes to the biological basis surrounding the pathophysiology of diseases triggered by these protein alterations.